Ultrathin high-thermal-conductivity graphite film and preparation method thereof

By adopting specific chemical imidation and mechanical stretching steps during the preparation of graphite film, the problem of structural defects and thermal conductivity of graphite films in the high-temperature graphitization process was solved, and an ultra-thin high-thermal conductivity graphite film was successfully prepared to achieve It takes into account both thermal conductivity and flexibility.

CN119430940APending Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411683756.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing graphite films are prone to microstructure defects during high-temperature graphitization, resulting in a decline in mechanical properties. At the same time, the modification method sacrifices flexibility and partial thermal conductivity to a certain extent.

Method used

Polyamic acid solution is synthesized by selecting dianhydride and diamine as monomers in a polar aprotic solvent, and is subjected to imidation treatment, and film formation through casting, heating imidation, infiltrating oil agent, uniaxial pre-pre- Ultra-thin high thermal conductivity graphite film is prepared by stretching and biaxial stretching.

Benefits of technology

It achieves a balance of ultra-thin flexibility and high thermal conductivity, meets the flexibility and lightweight needs of aerospace and portable electronic equipment, while improving the thermal conductivity and mechanical properties of graphite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430940A_ABST
    Figure CN119430940A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin high-thermal-conductivity graphite film and a preparation method thereof, and belongs to the technical field of graphite films. The method specifically comprises the following steps: (1) synthesizing a polyamide acid solution and carrying out chemical imidization to obtain a polyimide film with a good aggregation structure; (2) the polyimide film is infiltrated with an oil agent, so that adhesion between films is reduced, and the film is prevented from being torn; (3) biaxial stretching is carried out after uniaxial pre-stretching; and (4) hot-pressing carbonization, graphitization and calendering are carried out, and the ultrathin high-thermal-conductivity flexible graphite film is obtained. The method is simple and rapid in process step, chemical imidization can promote formation of a graphite structure with ordered interlayer arrangement, and the heat conductivity of the graphite film is improved. And the wetting oil agent can increase the lubricating effect, so that the multi-layer polyimide film is prevented from being torn in the stretching process. Through uniaxial prestretching, preliminary orientation is provided for the film, the mechanical property is enhanced, the stability of the multilayer film in the biaxial stretching process is promoted, and the heat-conducting property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of graphite films, and in particular to an ultra-thin high thermal conductivity graphite film and a preparation method thereof. Background Art

[0002] In recent years, as modern electronic devices have gradually developed towards multifunctionality, portability, lightness, and miniaturization, the integration and power density of high-performance electronic devices have continued to increase, and heat dissipation has become one of the key factors affecting the stability and life of equipment. Traditional heat dissipation materials are mainly metal materials, such as metal heat sinks, which can no longer meet the growing heat dissipation needs due to their large volume and mass and strong rigidity. Therefore, the development of heat dissipation materials with both high thermal conductivity and ultra-thin flexibility has become a research focus in the current technology field.

[0003] High thermal conductivity graphite film is a new type of thermal conductive material developed in recent years. It has the characteristics of high temperature resistance, light weight, high thermal conductivity, strong chemical stability, and small thermal expansion coefficient. It has become an important material for electronic equipment in the 5G era to break through the "heat dissipation" problem. Graphite materials have the characteristics of high thermal conductivity and electrical conductivity, good chemical stability and thermal stability. Due to its unique layered structure, graphite film materials have extremely high thermal conductivity in the planar direction. The thermal conductivity of artificial graphite film can reach up to 1900 W / (m·K). At present, most graphite films have a thickness of 20~200 μm and a density of 1.0-1.9 g / cm 3 , thermal conductivity 700-1300 W / (m·K). However, the battery thermal management systems in smartphones, tablets, aerospace, communication equipment and new energy vehicles require efficient heat conduction at a very small thickness. Therefore, graphite film needs to have ultra-thin properties while maintaining excellent thermal conductivity.

[0004] Polyimide-based graphite films have excellent properties of high thermal conductivity, light weight and flexibility. However, due to the structural characteristics of polyimide molecules, microstructural defects are prone to occur during high-temperature graphitization, resulting in a decrease in the mechanical properties of the film. Therefore, researchers have modified the polyimide substrate before carbonization or graphitization, such as introducing thermally conductive fillers such as graphene and carbon nanotubes, to enhance the overall structural strength of the film. However, these modification methods sacrifice the flexibility and partial thermal conductivity of the graphite film to a certain extent. Therefore, there is an urgent need for a graphite film with high thermal conductivity and. Summary of the invention

[0005] The purpose of the present application is to provide an ultra-thin high thermal conductivity graphite film and a preparation method thereof. The preparation method is simple and low-cost, while achieving the advantages of ultra-thin flexibility and high thermal conductivity, meeting the flexibility and lightweight requirements of aerospace and portable electronic devices.

[0006] The preparation method of ultra-thin high thermal conductivity graphite film is as follows: S1, selecting dianhydride and diamine as monomers to synthesize a polyamic acid solution through a polycondensation reaction in a polar aprotic solvent; S2, a catalyst and a dehydrating agent are mixed, and added to the polyamic acid solution obtained in S1 for imidization treatment, and after the reaction, the mixture is placed at low temperature for degassing to obtain a treated polyamic acid solution; S3, casting the treated polyamic acid solution obtained in S2 into a film, and then heating the film for imidization at a temperature of 200-400° C. to obtain a polyimide film; S4, soaking the polyimide film obtained in S3 in an oil agent to obtain a polyimide film soaked in the oil agent; S5, after stacking the polyimide films impregnated with the oil agent, perform uniaxial pre-stretching, perform pre-orientation, and then perform biaxial stretching, and naturally cool after stretching to obtain a single-layer polyimide film.

[0007] S6, soaking the single-layer polyimide film in a cleaning agent to remove oil residue, and drying and volatilizing the solvent after cleaning to obtain a treated single-layer polyimide film; S7, carbonizing and graphitizing the treated single-layer polyimide film to obtain a graphite film; S8. Place the graphite film on a calender to obtain an ultra-thin high thermal conductive graphite film.

[0008] Preferably, in S1, the dianhydride monomer is one of pyromellitic dianhydride and biphenyltetracarboxylic dianhydride, the diamine monomer is one of 4,4'-diaminodiphenyl ether, p-phenylenediamine and m-phenylenediamine, and the reaction temperature is -5°C to 0°C.

[0009] Preferably, in S2, the catalyst includes a compound containing a tertiary amine structure, such as one of pyridine, triethylamine, triethylamine alcohol, 3-methylpyridine, isoquinoline, and 2,6-lutidine, the dehydrating agent is one of acetyl chloride, thionyl chloride, and aliphatic anhydride, and the molar ratio of the catalyst to the dehydrating agent is 5moL:1moL-1moL:5moL.

[0010] Preferably, in S3, the heating step is: the film is placed in a muffle furnace, heated from room temperature to 100°C at a rate of 3°C / min, and kept warm for 1 hour; the temperature is continued to be increased to 200°C at a rate of 3°C / min, and kept warm for 1 hour; and the temperature is further increased to 350°C at a rate of 3°C / min, and kept warm for 1 hour.

[0011] Preferably, in S4, the oil agent is polydimethylsiloxane, cyclohexylmethylsiloxane, phenylsiloxane or mineral oil, and the immersion time is 0.5 to 4 hours.

[0012] Preferably, in S5, the stretching temperature in the uniaxial pre-stretching operation is 250~400°C, the stretching rate is 0.5~50% / s, and the stretching ratio is 1~3 times; the stretching temperature in the biaxial stretching operation is 300~450°C, the stretching rate is 1~50% / s, and the stretching ratio is 1.5~5 times.

[0013] Preferably, in S6, the cleaning agent includes one of isopropanol, ethanol, toluene, xylene, petroleum ether, chloroform, octanol, and turpentine, and the immersion time is 0.25 to 2 hours.

[0014] Preferably, in S7, the carbonization temperature is 800°C~1500°C, the heating rate is 2~5°C / min, the insulation is 1~4h, the pressure is 0.05~4MPa, and nitrogen is always introduced during the carbonization process; the graphitization temperature is 2400~3000°C, the heating rate is 2~5°C / min, the insulation is 1~4h, the pressure is 0.05~4MPa, and argon is always introduced during the graphitization process.

[0015] Preferably, in S8, the thickness of the formed graphite film is 10-25 μm, and the thermal conductivity is 1400-1900 W / (m·K).

[0016] The present application provides an ultra-thin high thermal conductivity graphite film obtained according to the above-mentioned method for preparing the ultra-thin high thermal conductivity graphite film.

[0017] Therefore, the present application provides an ultra-thin high thermal conductivity graphite film and a preparation method thereof, which has the following beneficial effects: 1. Through the method of chemical imidization, a polyimide film with good aggregation structure and high imidization is obtained, which promotes the formation of a graphite structure with orderly interlayer arrangement, large grain size and small lattice defects, thereby improving the thermal conductivity of the graphite film.

[0018] 2. The oil has a lubricating effect, which can reduce the adhesion between films, ensure that the multilayer film has good uniformity during the stretching process, and avoid film tearing.

[0019] 3. Uniaxial pre-stretching can provide initial orientation for the film and enhance the mechanical properties of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a SEM image of the graphite film prepared corresponding to Example 1; Figure 2 This is a SEM image of a graphite film with many defects obtained in Comparative Example 1 without chemical imidization; Figure 3 is a SEM image of the graphite film prepared corresponding to Example 2; Figure 4 This is a SEM image of the surface cracks obtained in Comparative Example 2 without oil infiltration; Figure 5 is a SEM image of the graphite film prepared in accordance with Example 3; Figure 6 This is a SEM image of Example 3 with low flatness obtained without uniaxial pre-stretching. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further illustrated by the following examples.

[0022] Example 1 (1) Preparation of polyamic acid solution: 8.1 g ODA was dissolved in 100 ml DMF and stirred evenly, and 8.8 g PMDA was added in batches while stirring continuously. The reaction temperature was controlled at -5°C to 0°C to obtain a PAA solution. (2) Chemical imidization: Mix the dehydrating agent acetic anhydride and the catalyst pyridine, wherein the acetic anhydride addition amount is 50 mol% and the acetic anhydride: pyridine = 1:1, add to the PAA solution obtained in step (1), fully react for 2 h, and stand at low temperature to remove bubbles for 24 h; (3) Film formation: The PAA solution is uniformly cast on a flat substrate to form a thin film, which is placed in a muffle furnace and heated from room temperature to 100°C at a rate of 3°C / min and kept at this temperature for 1 hour; the temperature is further increased to 200°C at a rate of 3°C / min and kept at this temperature for 1 hour; the temperature is further increased to 350°C at a rate of 3°C / min and kept at this temperature for 1 hour to achieve imidization and obtain a polyimide film; (4) impregnation oil: the polyimide film obtained in step (3) is impregnated in polydimethylsiloxane for 2 hours to obtain a polyimide film impregnated with oil; (5) Stretching: Ten sheets of polyimide films soaked in oil were taken out and stacked for simultaneous uniaxial pre-stretching of the multilayer films. The temperature was maintained at 280 °C for 5 min, the stretching ratio was 1.5 times, and the stretching rate was 10% / s. The multilayer films were biaxially stretched at 320 °C for 10 min, the stretching ratio was 2.5 times, and the stretching rate was 35% / s. A single-layer polyimide film of 15-30 μm was successfully separated. (6) Cleaning the oil: Soak the single-layer polyimide film in isopropanol for 40 minutes and stir gently; place the film in new isopropanol for 20 minutes for secondary cleaning to remove the oil residue. After cleaning, place it in a 60℃ forced air oven to dry for 0.5-2 hours to ensure that the solvent is completely evaporated; (7) Hot pressing carbonization and graphitization: the single-layer polyimide film obtained in step (6) after the solvent is evaporated is placed in a mold and placed in a carbonization furnace, and the temperature is slowly increased from room temperature to 1400°C, the carbonization rate is 3°C / min, the pressure is 0.1 MPa, and nitrogen is always introduced during the carbonization process and the temperature is kept for 2 hours; after carbonization, the film is placed in a graphitization furnace, and the temperature is slowly increased from room temperature to 2800°C, the graphitization rate is 3°C / min, the pressure is 0.1 MPa, and argon is always introduced during the graphitization process and the temperature is kept for 2 hours; (8) Calendering: Place the graphite film on a calender and calender it multiple times until the thickness of the film reaches 10 μm. A single-layer 10 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1800 W / (m·K).

[0023] Example 2 The immersion time in polydimethylsiloxane in step (4) was shortened to 1 h, and the other conditions were the same as those in Example 1.

[0024] A single-layer 12 μm extremely thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1793 W / (m·K). Compared with the untreated graphite film, the thickness was significantly reduced and the thermal conductivity was significantly improved.

[0025] Example 3 The temperature of the uniaxial pre-stretching in step (5) was adjusted to 260°C, and the other conditions were the same as those in Example 1.

[0026] A single-layer 10 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1592 W / (m·K).

[0027] Example 4 The temperature of biaxial stretching in step (5) was increased to 350°C, and the other conditions were the same as those in Example 1.

[0028] A single-layer 11 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1752 W / (m·K).

[0029] Example 5 The stretching ratio of the uniaxial pre-stretching in step (5) was increased to 2 times, and the other conditions were the same as those in Example 1.

[0030] A single-layer 14 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1476 W / (m·K).

[0031] Example 6 The stretching ratio of the biaxial stretching in step (5) was increased to 3 times, and the other conditions were the same as those in Example 1.

[0032] A single-layer 10 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1692 W / (m·K).

[0033] Example 7 The stretching rate of the uniaxial pre-stretching in step (5) is 20% / s, and the other conditions are the same as those in Example 1.

[0034] A single-layer 14 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1563 W / (m·K).

[0035] Example 8 The stretching speed of the biaxial stretching in step (5) was increased to 45% / s, and the other conditions were the same as those in Example 1.

[0036] A single-layer 12 μm thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1621 W / (m·K).

[0037] Comparative Example 1 The PAA solution obtained in step (1) is directly formed into a film without the chemical imidization treatment in step (2). Other conditions are the same as those in Example 1.

[0038] A single layer of 15 μm extremely thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1420 W / (m·K).

[0039] Comparative Example 2 The polyimide film obtained in step (3) is directly subjected to the stretching treatment in step (5) without the impregnation oil in step (4). The other steps and conditions are the same as those in Example 1.

[0040] A single-layer 16 μm extremely thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1401 W / (m·K).

[0041] Comparative Example 3 The polyimide impregnated with oil obtained in step (4) is directly subjected to biaxial stretching treatment in step (5) without uniaxial pre-stretching in step (5). Other conditions are the same as those in Example 1.

[0042] A single layer of 15 μm extremely thin graphite film was obtained. The thermal conductivity of the film was tested and found to be 1413 W / (m·K).

[0043] Comparative Example 4 After the film is formed in step (3), the film is placed in a muffle furnace and heated from room temperature to 350°C at a rate of 3°C / min and kept warm for 1 hour to achieve imidization and obtain a polyimide film. Other conditions are the same as those in Example 1.

[0044] A single layer of extremely thin graphite film with a thickness of 15 μm was obtained. The thermal conductivity of the film was tested and found to be 1523 W / (m·K).

[0045] The graphite films obtained in Example 1 and Comparative Examples 1-4 were subjected to a tensile strength test. Samples of the same size and shape were selected, tensile force was applied to the samples at the same speed, and the force value and deformation during the loading process were recorded; when the sample broke, the force value and deformation at the time of breaking were recorded.

[0046] Tensile strength = breaking force / sample cross-sectional area. The obtained tensile strength data are shown in Table 1.

[0047] Table 1 Tensile strength table

[0048] Therefore, the present application provides an ultra-thin high thermal conductivity graphite film and a preparation method thereof, wherein the process steps of the method are simple and rapid, chemical imidization can promote the formation of an orderly interlayer graphite structure, improve the thermal conductivity of the graphite film, and the impregnation oil can increase the lubrication effect and prevent the multilayer polyimide film from tearing during the stretching process. The uniaxial pre-stretching provides the film with a preliminary orientation, enhances the mechanical properties, promotes the stability of the multilayer film during the biaxial stretching process, and improves the thermal conductivity.

[0049] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0050] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an ultra-thin high thermal conductivity graphite film, characterized in that: The preparation method of ultra-thin high thermal conductivity graphite film is as follows: S1, selecting dianhydride and diamine as monomers to synthesize a polyamic acid solution through a polycondensation reaction in a polar aprotic solvent; S2, a catalyst and a dehydrating agent are mixed, and added to the polyamic acid solution obtained in S1 for imidization treatment, and after the reaction, the mixture is placed at low temperature for degassing to obtain a treated polyamic acid solution; S3, casting the treated polyamic acid solution obtained in S2 into a film, and then heating the film at a temperature of 200-400° C. to obtain a polyimide film; S4, soaking the polyimide film obtained in S3 in an oil agent to obtain a polyimide film soaked in the oil agent; S5, after stacking the polyimide films impregnated with the oil agent, perform uniaxial pre-stretching, perform pre-orientation, and then perform biaxial stretching, and naturally cool after stretching to obtain a single-layer polyimide film. S6, soaking the single-layer polyimide film in a cleaning agent to remove oil residue, and drying and volatilizing the solvent after cleaning to obtain a treated single-layer polyimide film; S7, carbonizing and graphitizing the treated single-layer polyimide film to obtain a graphite film; S8. Place the graphite film on a calender to obtain an ultra-thin high thermal conductive graphite film.

2. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 1, characterized in that: In S1, the dianhydride monomer is one of pyromellitic dianhydride and biphenyltetracarboxylic dianhydride, the diamine monomer is one of 4,4'-diaminodiphenyl ether, p-phenylenediamine and m-phenylenediamine, and the reaction temperature is -5°C to 0°C.

3. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 2, characterized in that: In S2, the catalyst includes a compound containing a tertiary amine structure, such as one of pyridine, triethylamine, triethylamine alcohol, 3-methylpyridine, isoquinoline, and 2,6-lutidine; the dehydrating agent is one of acetyl chloride, thionyl chloride, and aliphatic anhydride; and the molar ratio of the catalyst to the dehydrating agent is 5moL:1moL-1moL:5moL.

4. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 3, characterized in that: In S3, the heating steps are as follows: the film is placed in a muffle furnace, heated from room temperature to 100°C at a rate of 3°C / min, and kept warm for 1 hour; the temperature is further increased to 200°C at a rate of 3°C / min, and kept warm for 1 hour; the temperature is further increased to 350°C at a rate of 3°C / min, and kept warm for 1 hour.

5. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 4, characterized in that: In S4, the oil agent is polydimethylsiloxane, cyclohexylmethylsiloxane, phenylsiloxane or mineral oil, and the immersion time is 0.5~4h.

6. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 1, characterized in that: In S5, the stretching temperature in the uniaxial pre-stretching operation is 250~400℃, the stretching rate is 0.5~50% / s, and the stretching ratio is 1~3 times; the stretching temperature in the biaxial stretching operation is 300~450℃, the stretching rate is 1~50% / s, and the stretching ratio is 1.5~5 times.

7. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 6, characterized in that: In S6, the cleaning agent includes one of isopropyl alcohol, ethanol, toluene, xylene, petroleum ether, chloroform, octanol, and turpentine, and the immersion time is 0.25 to 2 hours.

8. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 7, characterized in that: In S7, the carbonization temperature is 800℃~1500℃, the heating rate is 2~5℃ / min, the insulation is 1~4h, the pressure is 0.05~4MPa, and nitrogen is always introduced during the carbonization process; the graphitization temperature is 2400~3000℃, the heating rate is 2~5℃ / min, the insulation is 1~4h, the pressure is 0.05~4MPa, and argon is always introduced during the graphitization process.

9. The method for preparing an ultra-thin high thermal conductivity graphite film according to claim 6, characterized in that: In S8, the thickness of the formed graphite film is 10~25 μm, and the thermal conductivity is 1500~1900 W / (m·K).

10. An ultra-thin high thermal conductivity graphite film obtained according to the method for preparing an ultra-thin high thermal conductivity graphite film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-thermal-conductivity graphite film, and preparation method and application thereof

    CN111017920A

  • High-heat-flux graphene-polyimide carbonized film as well as preparation method and application thereof

    CN112919452A

  • Preparation method of carbon fiber reinforced high-strength and high-thermal-conductivity composite film

    CN113402288A

  • High-safety diaphragm as well as preparation method and application thereof

    CN113904061A

  • Polyimide-based high-thermal-conductivity graphite film

    CN114014657A